Abrogation of lectin-like oxidized LDL receptor-1 attenuates acute myocardial ischemia-induced renal dysfunction by modulating systemic and local inflammation - Lu, Jingjun (2012)
It is assumed that acute myocardial infarction affects renal function. To study the mechanism, we used mice following permanent ligation of their left coronary artery that results in extensive myocardial infarction. Soon after ligation, there was a marked rise in circulating pro-inflammatory cytokines and malondialdehyde (thiobarbituric acid-positive evidence of lipid peroxidation). Renal function had significantly declined by the third day in association with mild fibrosis, and swelling of glomeruli and tubules. There was a significant increase in the expression of the lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1), interelukin-1β, vascular cell adhesion molecule-1, and thiobarbituric acid-reactive substances in the kidney. Renal function showed some recovery by Day 21; however, there was progressive fibrosis of the kidneys. LOX-1 knockout mice had significantly diminished increases in systemic and renal pro-inflammatory cytokines, malondialdehyde, structural alterations, and decline in renal function than the wild-type mice following ligation of the left coronary artery. Cardiac function and survival rates were also significantly better in the LOX-1 knockout mice than in the wild-type mice. Hence, severe myocardial ischemia results in renal dysfunction and histological abnormalities suggestive of acute renal injury. Thus, LOX-1 is a key modulator among multiple mechanisms underlying renal dysfunction following extensive myocardial infarction.